GE_GERICHTE P/9253/2018 vom 28. April 2025 - GE Cour de justice (2025)
PLAIGNANT;RETRAIT(VOIE DE DROIT);INDIVISIBILITÉ;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DÉNONCIATION CALOMNIEUSE | CPP.310; CPP.120; CP.303; CP.33